Efektivitas Komunikasi Kegiatan "COFFEE MORNING" Pada Pt Pelindo Regional III - Elrizfa Deviona; Imelda Dwi Putri Nainggolan; Putri Alifiah Widyawan; Dyva Claretta; Ahimsa Adi (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
This study aims to find out how the effectiveness and output generated from the Coffee Morning public relations program by PT Pelindo Regional III as an effort to threaten bureaucratic problems externally to public companies. The research method used is qualitative research with in-depth interviews. The results of this study indicate that the event titled Coffee Morning runs effectively and also produces the expected output such as conveying information related to changes in the company that is well received by stakeholders and also strengthening the bond between stakeholders and the company.